2015
DOI: 10.3390/nu7053347
|View full text |Cite
|
Sign up to set email alerts
|

Bones of Contention: Bone Mineral Density Recovery in Celiac Disease—A Systematic Review

Abstract: Metabolic bone disease is a frequent co-morbidity in newly diagnosed adults with celiac disease (CD), an autoimmune disorder triggered by the ingestion of dietary gluten. This systematic review of studies looked at the efficacy of the gluten-free diet, physical activity, nutrient supplementation, and bisphosphonates for low bone density treatment. Case control and cohort designs were identified from PubMed and other academic databases (from 1996 to 2015) that observed newly diagnosed adults with CD for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 86 publications
1
46
0
1
Order By: Relevance
“…. Their observations were also confirmed by experimental data obtained from observational or cohort studies and National Diet and Nutrition Surveys (Kupper 2005;Hallert and others 2009;Ohlund and others 2010;Saturni and others 2010;Caruso and others 2013;Martin and others 2013;Penagini and others 2013;Shepherd and Gibson 2013;Samasca and others 2014;Theethira and others 2014;Grace-Farfaglia 2015) that stressed how some deficiencies can be encountered at the diagnosis because of malabsorption following villi atrophy, but also originate from the poor quality of GF products and avoidance of several kinds of foods naturally rich in these micro-and/or macronutrients.…”
Section: Nutritional Quality Of Conventional Compared With Gf Breadmentioning
confidence: 63%
“…. Their observations were also confirmed by experimental data obtained from observational or cohort studies and National Diet and Nutrition Surveys (Kupper 2005;Hallert and others 2009;Ohlund and others 2010;Saturni and others 2010;Caruso and others 2013;Martin and others 2013;Penagini and others 2013;Shepherd and Gibson 2013;Samasca and others 2014;Theethira and others 2014;Grace-Farfaglia 2015) that stressed how some deficiencies can be encountered at the diagnosis because of malabsorption following villi atrophy, but also originate from the poor quality of GF products and avoidance of several kinds of foods naturally rich in these micro-and/or macronutrients.…”
Section: Nutritional Quality Of Conventional Compared With Gf Breadmentioning
confidence: 63%
“…More impressively, a five‐year follow‐up study of 22 adult patients with newly diagnosed CD demonstrated that the compliance with a gluten‐free diet improved bone mineral density and normalized vitamin D status in all but two patients . In general, it appears that a long‐term, gluten‐free diet plus supplementation of calcium and high doses of vitamin D is helpful for patients with CD …”
Section: Vitamin D Supplementation For Patients With Cdmentioning
confidence: 99%
“…It is a genetically predisposed persons as a consequence of autoimmune disorder affecting the gastrointestinal system resulting in inflammation and damage to the lining of the small intestine [2]. Celiac disease reduces absorption of nutrients iron, calcium, vitamins A, D, E, K and folate for these group consumers, who around 1% of the population in USA and Europe [3].…”
Section: Introductionmentioning
confidence: 99%